Regression Analysis of Preoperative Chest Radiographs to Predict Intraoperative Location of Esophageal Foreign Body (Coin) in Pediatric Patients - Angelika Doreen Martinez; Fortuna Corazon Roldan (Philippine Journal of Otolaryngology Head and Neck Surgery)
Objectives: To provide a guide to estimate the location of coins within the esophagus based on the pre-operative radiographic image among pediatric patients seen at the East Avenue Medical Center Department of Otorhinolaryngology – Head and Neck Surgery (ORL-HNS) between January 2018 and December 2020.